The level of gender bias in workplace and household / Muhammad Saufi Zulqaram … [et al.] - Zulqaram, Muhammad Saufi; Zainal, Hani Suraya Harni; Mahat, Nurfatihah Farahin; Sultan Mohideen, Rosilawati; Ilyas, Ilya Yasnoriza; Ramlan, Aini Faezah; Jaapar, Iqbal; Suyurno, S Salahudin; Amairudin, Muhammad Firdaus (Faculty of Communication & Media Studies, 2021)
Gender bias occurs when a person prefers one gender over another, resulting in unconscious bias or stereotypes directed against another member of a group, such as at work or at home. The aim of this study is to look at the level of how much gender bias exists in the workplace and household in Malaysia. The theory that has been used as a guideline for this research is Symbolic Interaction Theory by George Herbert Mead. An online questionnaire with 11 items for demographic section and 18 items was designed in order to evaluate the level of gender bias that exists in the workplace and household from all around Malaysia. The study involved 435 respondents consisting of the public with various backgrounds by using Google Form platform. The amount of the survey calculated based on the table, N=435. There are two main elements designed in this research in order to measure the level of gender bias in the workplace and the household in Malaysia. All variables were measured through the scale previously used by another researcher and scale of approval from 1 (Strongly disagree) - 4 (Strongly agree). The result of the research indicate that the level of gender bias exists the most is in workplace (M=3.32) followed by household (M=3.07)